Fulfillment Of Assimilation Rights And Integration Rights To Corporate Students - Susan Bau; Zamroni Abdussamad; Waode Mustika (Universitas Negeri Gorontalo, 2022)
This study aims to determine the fulfillment of assimilation rights and integration rights to correctional students. The type of research method used in this study is empirical research with sampling using purposive sampling. This study also uses a qualitative approach and descriptive analysis techniques. The results of this study indicate thatIn the implementation of the fulfillment of the right of assimilation and the right of integration to correctional students, there are several obstacles, as for these obstacles, namely there is no guarantor of the correctional students, has register f records, Community Environment, excess capacity, minimal quality of officers and less bureaucratic processes. effective. The government carries out alternative non-prison punishments that can be carried out such as supervision and community service which is seen as more efficient than prison law because in achieving the goal of fostering or rehabilitating correctional students before finally being able to be free and return to life in the community and for the community.The community is expected to participate actively in the implementation of community programs, so that correctional students feel they can be accepted again in the community.